An Efficient Palladium-Thiourea Catalysed Heck Cross-Coupling Reaction for Molecular Electronic Interest - Khairul, Wan M.; Md Shariff, Mohd Shahrul Shahmi; Rahamathullah, Rafizah; Daud, Adibah Izzati; Shamsuddin, Mustaffa; Che Soh, Siti Kamilah (UI Scholars Hub, 2017)
The synthesis and utilization of C-C bonds formation are concerned about the key steps for the building of several conducting molecular electronics involving many asymmetric catalysts approached, which is an essential task that most researchers would ignore in preparing these materials to enhance the production yield of cross-coupling materials. Despite the enormous progress, there still remains a great demand for economic and practicable cross-coupling processes involving ultra-low catalyst loadings with high turnover numbers due to the employment of conventional metal catalyst. Thus, there has been an excessive interest to cultivate non-phosphine palladium catalysts for excellent achievement of activity, stability, and substrate tolerance which permit the coupling reactions to be conducted under mild reaction condition at ambient atmosphere. In this contribution, N-(4-nitrophenylcarbamothioyl)-N’-(4- methylbenzoyl) thiourea (LT1) and its metal complex of MLT1 featuring Pd (II) have been successfully characterised via typical spectroscopic methods namely; Infrared (IR) spectroscopy, Ultraviolet-visible (UV-Vis) spectroscopy, CHNS elemental analysis, and Nuclear Magnetic Resonance (1H and 13C NMR). In turn, catalytic studies of palladium catalyst (MLT1) were tested for its homogenous catalytic activity in Heck cross-coupling reaction. The reaction was monitored by Gas Chromatography-Flame Ionisation Detector (GC-FID). Results reveal that MLT1 exhibits 100% of conversion starting material into a cross-coupling product, which was alkene-based compound.